Understanding the Role of Host Hemocytes in a Squid/Vibrio Symbiosis Using Transcriptomics and Proteomics - Collins, Andrew J.; Schleicher, Tyler R.; Rader, Bethany A.; Nyholm, Spencer V. (Frontiers in Immunology, 2012)
The symbiosis between the squid, Euprymna scolopes, and the bacterium, Vibrio fischeri, serves as a model for understanding interactions between beneficial bacteria and animal hosts. The establishment and maintenance of the association is highly specific and depends on the selection of V. fischeri and exclusion of non-symbiotic bacteria from the environment. Current evidence suggests that the host’s cellular innate immune system, in the form of macrophage-like hemocytes, helps to mediate host tolerance of V. fischeri. To begin to understand the role of hemocytes in this association, we analyzed these cells by high-throughput 454 transcriptomic and liquid chromatography/ tandem mass spectrometry (LC-MS/MS) proteomic analyses. 454 high-throughput sequencing produced 650,686 reads totaling 279.9 Mb while LC-MS/MS analyses of circulating hemocytes putatively identified 702 unique proteins. Several receptors involved with the recognition of microbial associated molecular patterns (MAMPs) were identified. Among these was a complete open reading frame (ORF) to a putative peptidoglycan recognition protein (EsPGRP5) that has conserved residues for amidase activity. Assembly of the hemocyte transcriptome showed EsPGRP5 had high coverage, suggesting it is among the 5% most abundant transcripts in circulating hemocytes. Other transcripts and proteins identified included members of the conserved NFκB signaling pathway, putative members of the complement pathway, the carbohydrate binding protein galectin, and cephalotoxin. Quantitative PCR of complement-related genes, cephalotoxin, EsPGRP5, and a nitric oxide synthase showed differential expression in circulating hemocytes isolated from adult squid with colonized light organs compared to those for which the symbionts were removed. These data suggest that the presence of the symbiont influences gene expression of the cellular innate immune system of the host.